2009
DOI: 10.1021/jp904243w
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Quantum Chemical Investigation of Chiroptical Properties of Nicotinamide Derivatives with and without Intramolecular Cation−π Interactions

Abstract: The circular dichroism (CD) spectra of neutral and cationic nicotinamide derivatives were experimentally examined in solution and in the solid state to show dramatic differences in the two phases and appreciable dependence on temperature and solvent. The CD spectrum of neutral nicotinamide 1 in solution was reproduced theoretically by averaging the theoretical spectra calculated for all of the extended and folded conformers (s-trans-G(+), s-cis-G(+), s-trans-T, and s-cis-T) weighted by their population. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…In addition, we found that when one of the terminal benzene moiety was kept at a fixed angle of 52° and the other was rotated, it was possible to reach the minimal barrier (14.3 kcal mol −1 ) for the conformation transfer. Under these conditions, the potential energy can be plotted as a function of the single dihedral angle and additionally according to the energy level a Boltzmann distribution at 25 °C can be obtained (see Figure S1 in the Supporting Information) 60. In agreement with the crystal measurements, 80 % of free molecules take the chair conformation at 25 °C, and in comparison the population of the boat conformer is less than 5 %.…”
Section: Resultssupporting
confidence: 63%
“…In addition, we found that when one of the terminal benzene moiety was kept at a fixed angle of 52° and the other was rotated, it was possible to reach the minimal barrier (14.3 kcal mol −1 ) for the conformation transfer. Under these conditions, the potential energy can be plotted as a function of the single dihedral angle and additionally according to the energy level a Boltzmann distribution at 25 °C can be obtained (see Figure S1 in the Supporting Information) 60. In agreement with the crystal measurements, 80 % of free molecules take the chair conformation at 25 °C, and in comparison the population of the boat conformer is less than 5 %.…”
Section: Resultssupporting
confidence: 63%
“…E p -E p/2 (Fc/Fc + ) = 70 mV (theoretically E p -E p/2 is 59/n mV where n is the number of electrons transferred in the redox reaction)] and peak current [almost 3¥ that for the Fc/Fc + couple at the same concentration (i p scales with n 3/2 )] are indicative of a two-electron reduction, and consistent with the formal addition of hydride ion to the nicotinamide cation ring, eqn (1). [13][14][15][16][17] The return sweep shows a broad peak at +0.51 V for re-oxidation of the dihydronicotinamide reduction product, i.e. the reverse of eqn (1).…”
mentioning
confidence: 99%
“…Electrocatalysis of hydrogen evolution is a characteristic of NAD + /H models. [13][14][15][16][17] The CVs of 1 to positive potentials are considerably complicated by oxidation processes arising from the dissociation of the iodide ion (see the ESI †). The electronic spectrum of 2 in the visible region is dominated by an interesting broad band centred at 466 nm (1650 M -1 cm -1 ).…”
mentioning
confidence: 99%
“…The spectra were shifted by 0.1 eV to better match with the experimental main‐band couplet. Further computational details are found elsewhere 33, 34…”
Section: Methodsmentioning
confidence: 99%